(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The research aims to demonstrate the importance of suppliers in activating manufacturing flexibility, and thus the research problem emerged from the reality of the challenges facing the General Company for Food Products, which require careful selection of suppliers and building good relations with them, which ensures the progress of the production process in a coordinated manner devoid of interruptions, which in turn achieve success for the researched company. An intentional sample of (83) individuals was adopted from (the general manager and his assistants and directors of departments and divisions), and the research included tests for a number of main and sub-hypotheses about the availability of correlation and influence relationships between its variables. spearman, coefficient of determination R2, (Test-F), (Test- Z) and linear regression analysis.The research reached a set of results, the most prominent of which was the presence of an effective influence role for suppliers in achieving manufacturing flexibility at the General Company for Food Products, and the suppliers’ financial position recorded the highest impact in activating manufacturing flexibility among the components of the suppliers.